Aplicação de uma técnica para melhoria da qualidade do sistema de produção da água de reuso: um estudo de caso de uma ETE do Estado de São Paulo - Nakamura, Sérgio Yoshiyuki (2017)
The current global water crisis makes awareness of the problem of its finiteness present in discussion, whether governmental, private, research, ecology or sustainability. The search for better forms of consumption and alternatives of treatment and production of reuse water is increasing importance and intensifying studies in those areas. The objective of this work was to analyze membrane filtration techniques for the treatment of sewage effluents generated by ETE, verifying the technical and economic feasibility of improving the quality of reuse water production in Brazil, specifically in the State of São Paulo, verifying the technical and economic viability. This state was selected because, in the years 2014 and 2015, it experienced an atypical drought that presented low rainfall indices that had not been counted for decades, resulting in a possible rationing of water for the population. An exploratory research was carried out about filter membranes and their applications and an on - site interview with the technical lider of a large sanitation company that produces reuse water from sanitary effluents with a quality 50% higher than required by the standards of potability using this technology. The results of this work indicated positive estimates for the investment in the use of filter membranes for the production of reuse water. Its cost in the plant was estimated at 0.10 R$ / m3 and the average sale price of 1,70 R$ / m3, allowing financial savings for the final consumer, in this case 90.26% / m3, and for the investor, according to those estimates, an attractive return on investment, with a payback of 7.31 years, for a 41-year contract.